Protection of Indigenous Traditional Knowledge in The Digital Economy Era: a Review of Customary Law and Intellectual Property Rights - Ari Purwadi (PT. Anagata Sembagi Education, 2026)
The traditional knowledge held by indigenous communities in Indonesia faces new threats with the development of the digital economy, ranging from data mining by generative artificial intelligence to the tokenization of non-fungible tokens (NFTs) without consent or benefit sharing for the originating communities. This study aims to analyze the conception of traditional knowledge from the perspective of customary law and the national intellectual property legal framework, and to formulate a protection model that is responsive to the challenges of the digital era. The study uses a normative juridical method with a legislative, conceptual, and comparative approach. The results show that customary law views traditional knowledge as communal ownership that is magical-religious and cross-generational, a character that has not been comprehensively accommodated in the Copyright Law, the Patent Law, or the Trademark and Geographical Indications Law. The digital economy presents specific challenges in the form of artificial intelligence data mining, NFT tokenization, cross-border commercialization, and the paradox of defensive documentation. This study recommends a five-element protection model, namely the acceleration of sui generis regulations, a digital database with layered access, the application of the principle of prior informed consent and benefit sharing, transparent artificial intelligence governance, and strengthening the institutional capacity of indigenous peoples, which need to be implemented in an integrated manner and harmonized with developments in international law, especially the WIPO Treaty on Intellectual Property, Genetic Resources and Related Traditional Knowledge in 2024.